2019
DOI: 10.1002/gcc.22725
|View full text |Cite
|
Sign up to set email alerts
|

Role of miRNAs in immune responses and immunotherapy in cancer

Abstract: In the past decade, the study of mechanisms of cancer immunity has seen a prominent boom, which paralleled the increased amount of research on the clinical efficacy of immune checkpoint blockade in several lethal types of cancers. This conspicuous effort has led to the development of successful immunotherapy treatment strategies, whose medical impact has been recognized by the awarding of 2018 Nobel Prize in Physiology or Medicine to the two pioneers of check point inhibitor research, Tasuku Honjo and James Al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
94
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(94 citation statements)
references
References 116 publications
0
94
0
Order By: Relevance
“…TMB has emerged as an independent biomarker to predict patient responses to treatment with ICIs, 18,19,49,50 and the negative predictive role of low TMB could not be overcome by the combination immunotherapy. 50 Several studies have shown to effectively measure TMB from liquid biopsies/blood, [51][52][53][54] this might be an alternative to the biopsies since it is less invasive and easily repeatable. However, TMB assessment by liquid biopsy must face the problem that the circulating DNA deriving from tumor cells is often only a small fraction of the circulating cell free DNA and it needs further investigation and may be clarified within the ongoing clinical trials.…”
Section: Discussionmentioning
confidence: 99%
“…TMB has emerged as an independent biomarker to predict patient responses to treatment with ICIs, 18,19,49,50 and the negative predictive role of low TMB could not be overcome by the combination immunotherapy. 50 Several studies have shown to effectively measure TMB from liquid biopsies/blood, [51][52][53][54] this might be an alternative to the biopsies since it is less invasive and easily repeatable. However, TMB assessment by liquid biopsy must face the problem that the circulating DNA deriving from tumor cells is often only a small fraction of the circulating cell free DNA and it needs further investigation and may be clarified within the ongoing clinical trials.…”
Section: Discussionmentioning
confidence: 99%
“…Immune response can be triggered by inflammatory mediators or cytokines produced by infectious cells through the transcriptional or post-transcriptional regulations. The expression of ncRNAs may be closely related to the development of immune cells (particularly monocytes, macrophages, NK cells, T helper cells, CD8 + T cells, and Treg cells) and the maintenance of immune system homeostasis (Cortez et al, 2019;Imamura & Akimitsu, 2014). For instance, lincRNA-Cox2 regulates the release of inflammatory mediators and cytokines by stimulation of TLR2 in bacterial infections (Carpenter et al 2013), and miR-155 exerts an antiproliferative effect on CD8 + T cells in response to the type I interferon signaling (Gracias et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…miRNAs participate in both innate and adaptive immunity by interacting with various immune cells, including monocytes, macrophages, NK cells and T helper cells, in differentiation, activation and other functions. The relationship between miRNAs and immunity has important effects on cancer progression …”
Section: The Role Of Mir‐212 In Cancermentioning
confidence: 99%
“…The relationship between miRNAs and immunity has important effects on cancer progression. 44 An earlier study on the biological functions of miRNA-212 found it to interact with the neurons as well as inflammation. 11 Studies performed recently demonstrated that miRNA-212-3p can interact with immune cells and inflammatory cytokines in the occurrence or development of cancer.…”
Section: Rophages Nk Cells and T Helper Cells In Differentiation Amentioning
confidence: 99%